18t+9=

Simple and best practice solution for 18t+9= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 18t+9= equation:


Simplifying
18t + 9 = 0

Reorder the terms:
9 + 18t = 0

Solving
9 + 18t = 0

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-9' to each side of the equation.
9 + -9 + 18t = 0 + -9

Combine like terms: 9 + -9 = 0
0 + 18t = 0 + -9
18t = 0 + -9

Combine like terms: 0 + -9 = -9
18t = -9

Divide each side by '18'.
t = -0.5

Simplifying
t = -0.5

See similar equations:

| 56y+21= | | F(x)=x*-3x+7 | | 14s+7= | | 4.2p=50.4 | | y=75x-2x^2 | | 12s-12= | | 70m=630 | | 5a+4a=8a-1 | | 3y^2-3y+38=0 | | cotgx=-0 | | -5m-1=4m+5 | | 3x^2-2x=2x^2-1 | | 4-6r+-4=22 | | x^4=A | | 4(4a-3)= | | x+(x*.1957)=400 | | 39-12x=7x-16x | | -5(-4x+6)=90 | | 34-x-9=2x+11 | | Nx=R-S^2 | | 6x^2-10=2x^2-30 | | R-S^2=Nx | | 4(7+6x)=-260 | | 20x^2+5= | | 4=-17-p | | 3a+6a=-18 | | x+1+(-2)-1-(-2x)=5-1-(-x) | | 3/4x-5=1_1/4x | | 17=1/2-x-9 | | (20x^2)-5= | | 9-4(m+5)+4m= | | 4(c-1)c=2 |

Equations solver categories